Delisting Brazilian Public Companies: Empirical Evidence about Corporate Governance Issues - Patricia Maria Bortolon; Annor da Silva Junior (BBR: Brazilian Business Review)
This paper prop oses to analyse the relationship between corporate governance and delisting process of public companies listed on the Brazilian Securities, Commodities and Futures Exchange (Bolsa de Valores, Mercadorias e Futuros de São Paulo – BM&FBovespa). The sample co mprises 86 voluntary delisting operations in 2008 - 2012 period and a matching sample with companies that remained public, identified here as “comparable”. A corporate governance index comprising four dimensions (ownership structure, ethics and conflicts of interest, disclosure and board of directors) and a set of 16 questions was used to analyse the two groups. As expected, delisted companies score lower than their comparable ones is the broad index. However, board of directors, disclosure and ethics and con flicts of interest dimensions didn’t show statistical significant differences between the two groups. In the ownership structure dimension the issues related to concentration of control differentiate the groups. Despite the mean differences, corporate gove rnance doesn’t seem to impact significantly the chances to delist in a model with ownership structure and financial variables.